2021
DOI: 10.7717/peerj.10979
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organic manure on fruit set, fruit retention, yield, and nutritional status in pomegranate (Punica granatumL. “Wonderful”) under water and mineral fertilization deficits

Abstract: This research was conducted on mature pomegranate (Punica granatum L. “Wonderful”) trees growing at a site located in North Coast, Matrouh Governorate, Egypt. The aim was to investigate the impacts of different irrigation regimes in combination with different fertilizer regimes on the fruit set, fruit retention, yield, and nutritional status of the trees. The experimental factors were arranged in a split-plot design, with four replicates per treatment combination. The results indicated that all of the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among the co-application treatments, the highest values for all parameters except acidity and TSS/acidity ratio were obtained with the 75% mineral + 25% organic fertilizer treatment. The organic fertilizer therefore seems to have directly and indirectly enhanced the physiochemical properties of the soil and the availability of nutrients ( Mahdy, 2012 ; Baghdadi et al, 2018 ; Abdel-Sattar et al, 2021 ). Similarly, Ray et al (2014) reported that the fruit of pomegranate plants treated with 300-g N + 1-kg neem cake per plant showed high TSS (12.29Bx), total sugar (10.74%), reducing sugar (9.78%), non-reducing sugar (1.09%), and ascorbic acid (21.93 mg 100 mL 1 juice) contents as well as low acidity (0.39%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the co-application treatments, the highest values for all parameters except acidity and TSS/acidity ratio were obtained with the 75% mineral + 25% organic fertilizer treatment. The organic fertilizer therefore seems to have directly and indirectly enhanced the physiochemical properties of the soil and the availability of nutrients ( Mahdy, 2012 ; Baghdadi et al, 2018 ; Abdel-Sattar et al, 2021 ). Similarly, Ray et al (2014) reported that the fruit of pomegranate plants treated with 300-g N + 1-kg neem cake per plant showed high TSS (12.29Bx), total sugar (10.74%), reducing sugar (9.78%), non-reducing sugar (1.09%), and ascorbic acid (21.93 mg 100 mL 1 juice) contents as well as low acidity (0.39%).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the effects of irrigation regimes on the nutritional aspects of pomegranate fruit, the physiological and production responses of pomegranate trees to water stress, or the effects of coapplying organic and mineral fertilizers under scarcity irrigation ( Holland, Hatib & Bar-Yaakov, 2009 ; Abdel-Sattar et al, 2021 ). Previous field studies in southeastern Spain have examined the effects of different deficit irrigation applications on yield performance ( Intrigliolo et al, 2013 ; Abdel-Sattar et al, 2021 ) and some fruit composition characteristics during fruit growth ( Mellisho et al, 2012 ). Recently, it was also shown that deficit irrigation in combination with organic manure/mineral fertilizer or organic manure alone could improve the marketable fruit of Wonderful pomegranate trees, which may be attributable to the organic manure reducing the water stress of the growing plants ( Abdel-Sattar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, water use efficiency (WUE), as an important measure of plant drought tolerance, depends on the coupled processes of photosynthesis and transpiration and can effectively respond to the water use strategy of crops [16]. Abdel-Sattar et al [17] showed that moderate deficit irrigation is beneficial to increasing pomegranate yield, commercial fruit percentage, and WUE. However, what level of irrigation can promote the growth of young apple trees under drip irrigation conditions still needs further research and study.…”
Section: Introductionmentioning
confidence: 99%